Render unto Caesar ecclesiastical politics in the reign of Queen Anne - Levis, R. Barry (Cambridge James Clarke & Company, 2022)
Cover -- Advert Page -- Book Title -- Copyright -- Dedication -- Contents -- List of Illustrations -- Introduction -- Chapter 1. Prologue, 1698-1702 -- Chapter 2. The Tory Ascendancy, 1702-04 -- Chapter 3. The Shifting Balance of Power, 1705-06 -- Chapter 4. Strife in the North: A Case Study of Local Ecclesiastical Politics -- Chapter 5. The Whig Supremacy, 1706-09 -- Chapter 6. The Sacheverell Trial, 1709-10 -- Chapter 7. The Return of the Tories, 1710-14 -- Chapter 8. Epilogue -- Bibliography -- Index -- Back Cover.
Literaturverzeichnis: Seite 217-229
Keywords: Electronic books